Case Report: ECMO-assisted tracheal reconstruction in a 30-week-gestation preterm infant with tracheal stenosis - Li, Zi-Hao; Li, Shi-Hao; Geng, Zhen-Yang; Wu, Bin; Sheng, Yin-Liang; Yuan, Ping; Li, Feng; Qi, Yu (Frontiers in Pediatrics, 2024)
Tracheal stenosis is a rare but life-threatening disease in preterm infants. Misdiagnosis as congenital tracheal stenosis is common, making surgical management challenging. This report presents a case of a preterm infant with tracheal stenosis and congenital heart malformation treated with ECMOassisted tracheal resection and end-to-end anastomosis. A male infant was born at 30 weeks of gestation with severe asphyxia, cardiac insufficiency, and pneumonia. Following failed medical treatment, fiberoptic bronchoscopy confirmed mid-tracheal to carinal stenosis. After a 2-week treatment course, ECMO-assisted tracheal resection and end-to-end anastomosis were performed successfully. This case confirms the feasibility of tracheal resection and end-to-end anastomosis in low-weight, preterm infants with tracheal stenosis born at 30 weeks gestation. The utilization of ECMO for oxygenation during surgery provides a clear surgical field and shorter operating time. Surgical intervention may be necessary for neonatal tracheal stenosis depending on the clinical presentation.